2014
DOI: 10.1590/0103-5150.027.004.ao03
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dry needling and ischemic pressure in the myofascial syndrome: controlled clinical trial

Abstract: Introduction Musculoskeletal pain is a common clinical condition and about 10% of the population have musculoskeletal disorder. Objective The aim of this study was to evaluate whether ischemic pressure and dry needling techniques are able to reduce the pain of patients with myofascial pain syndrome. Method 22 patients aged 20-75 years were randomized into 3 groups: ischemic pressure (IPG = 8), dry needling (DNG = 7) and control (CG = 7). Patients in the IPG and DNG were assessed before and after 10 interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 21 publications
0
14
0
2
Order By: Relevance
“…After the full review process, 12 studies were selected for inclusion. 2,7,12,24,27,28,32,33,35,36,38,43 After contact with primary authors of included studies, 1 further study was identified for inclusion, 6 resulting in a total of 13 studies. The absolute degree of rater agreement for the first and second stages of the study selection was 86% and 93%, respectively.…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…After the full review process, 12 studies were selected for inclusion. 2,7,12,24,27,28,32,33,35,36,38,43 After contact with primary authors of included studies, 1 further study was identified for inclusion, 6 resulting in a total of 13 studies. The absolute degree of rater agreement for the first and second stages of the study selection was 86% and 93%, respectively.…”
Section: Study Selectionmentioning
confidence: 99%
“…This systematic review focused on musculoskeletal pain and included 13 studies: 6 on neck pain (5 on mechanical neck pain 6,24,28,32,43 and 1 on chronic whiplash-associated disorder 38 ), 1 on postoperative shoulder pain, 2 1 on chronic lower back pain, 33 1 on total knee arthroplasty, 27 1 on chronic ankle instability, 35 2 on myofascial pain, 12,36 and 1 on fibromyalgia. 7 Inclusion and exclusion criteria varied greatly across the studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations